Novel magnetic cation column [5] arene porous polymer as well as preparation method and application thereof

By developing a magnetic cationic pillar [5] aromatics and porous polymer (PP5-1F-MNP) as an adsorbent, combined with magnetic solid phase extraction and high-efficiency liquid chromatography-tandem mass spectrum method, the whole fluoride compound (PFCS) in the environmental water sample (PFCS) The problem of detection has achieved efficient and accurate PFCS detection and analysis.

CN119346086AActive Publication Date: 2025-01-24SOUTH CENTRAL UNIVERSITY FOR NATIONALITIES

Patent Information

Application Number
CN202411360738.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-24
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The prior art is difficult to accurately and reliably detect perfluoro compounds (PFCs) in ambient water samples due to their extremely low content in the environment and complex matrix effects.

Method used

Developed a magnetic cationic pillar [5] Gramocyric polymer polymer (PP5-1F-MNP), which reacts with 3-fluoropyridine reactions to generate cedic columns [5] aromatic hydrocarbon with FE3O4 nanometer particles with 3-fluoropyridine reactions. Combine to form a magnetic adsorbent. This adsorbent is detected by magnetic solid-phase extraction to assist high-efficiency liquid chromatography-MSPE-HPLC-MS/MS.

Benefits of technology

The efficient and quantitative analysis of PFCS in environmental water samples has the advantages of good linear, high recovery rate, low detection limit, high sensitivity, and good reproducibility. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346086A_ABST
    Figure CN119346086A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation, analysis and detection of new materials, and particularly relates to synthesis of a magnetic cation column [5] arene porous polymer PP5-1F-MNP and a new method for constructing a magnetic solid phase extraction assisted high performance liquid chromatography-tandem mass spectrum based on the PP5-1F-MNP. According to the PP5-1F-MNP, Fe3O4 nano particles serve as a core, column [5] arene porous polymer PP5-1F is coated outside the Fe3O4 nano particles, column [5] arene and 3-fluoropyridine are subjected to an electrophilic substitution reaction to generate PP5-1F, then a one-pot solvothermal method is utilized, the PP5-1F and FeCl3. 6H2O are subjected to a reaction, and the PP5-1F-MNP is prepared. The novel method for magnetic solid phase extraction assisted high performance liquid chromatography-tandem mass spectrometry based on PP5-1F-MNP can be used for quantitative analysis of C8-C14 long-chain PFCs at the same time, can be used for detection of trace PFCs in an actual sample, and provides a novel method and idea for enrichment and detection of PFCs in a complex matrix sample. Meanwhile, the huge potential of the pillararene material in the field of adsorption is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new material preparation and analysis and detection, and specifically relates to the synthesis of a novel magnetic column [5] aromatic porous polymer (PP5-1F-MNP) and a new method for constructing a magnetic solid phase extraction assisted high performance liquid chromatography-tandem mass spectrometry (PP5-1F-MNP MSPE-HPLC-MS / MS) based on PP5-1F-MNP, and is applied to the detection of perfluorinated compounds (PFCs) in environmental water samples. Background Art

[0002] Perfluorinated compounds (PFCs) are common persistent organic pollutants, widely used in consumer and industrial production. However, the accumulation of PFCs has caused environmental safety issues and has been detected worldwide, posing a threat to ecology and human health. However, the content of PFCs in the environment is extremely low, and there are complex matrix effects, which make it difficult to detect with conventional methods. Therefore, sample pretreatment is crucial.

[0003] Adsorption technology can enrich and separate PFCs and improve detection accuracy. Traditional adsorbents such as carbon nanotubes, activated carbon and graphene oxide have limitations, such as difficulty in separation and high regeneration costs. It is still necessary to continuously design and synthesize new adsorbent materials and develop highly sensitive and selective methods to detect and remove PFCs in the environment.

[0004] Pillar[n]arene, as a new generation of macrocyclic compounds, has become a very promising candidate for constructing supramolecular polymer materials with enhanced performance and functions due to its unique columnar structure, nanoscale cavity, multifunctional groups and excellent host-guest complexing ability. It is widely used in drug release platforms, fluorescent probes, sensors, detection, gas adsorption, water pollution treatment and photocatalysis. Its special structural characteristics give it excellent adsorption and recognition capabilities, enabling it to accurately capture and separate target compounds in complex environments. At the same time, the presence of multifunctional groups provides pillar aromatics with abundant reaction sites, allowing it to regulate its performance through chemical modification to meet the needs of adsorbing different pollutants.

[0005] Magnetic solid phase extraction (MSPE) is a technology that uses magnetic or magnetizable materials as adsorbents to separate and pre-concentrate target analytes in sample matrices. MSPE is to add magnetic adsorbents to solutions or suspensions containing target analytes to adsorb the target analytes. After the adsorption reaches equilibrium, the solution and the magnetic material are quickly separated by an external magnetic field, which improves the extraction efficiency and analysis accuracy. It provides strong support for research in the fields of chemical analysis, environmental monitoring, and biomedicine. Summary of the invention

[0006] In order to solve the problem that the traditional method for detecting PFCs is difficult to accurately and reliably determine its content, the present invention first generates a cationic column [5] aromatic hydrocarbon (PP5-1F) by electrophilic substitution reaction between brominated functional group column [5] aromatic hydrocarbon and 3-fluoropyridine, and then uses a one-pot solvent thermal method to react PP5-1F with FeCl3·6H2O in a high-pressure reactor to successfully construct a magnetic cationic column [5] aromatic hydrocarbon polymer material (PP5-1F-MNP). The present invention develops a magnetic column [5] aromatic hydrocarbon polymer material with both efficient adsorption and easy separation and regeneration characteristics, and constructs a magnetic solid phase extraction assisted high performance liquid chromatography-tandem mass spectrometry method (PP5-1F-MNP MSPE-HPLC-MS / MS) based on the magnetic cationic column [5] aromatic hydrocarbon polymer material (PP5-1F-MNP) to detect PFCs in complex matrix samples, providing a new technical path for environmental protection and pollution control.

[0007] In order to accurately detect the content of PFCs at environmental level concentrations and in complex matrices, the present invention provides a magnetic cation column [5] aromatic polymer material PP5-1F-MNP, wherein the PP5-1F-MNP has Fe3O4 nanoparticles as the core, and the cation column [5] aromatic polymer PP5-1F is coated on the outside of the Fe3O4 nanoparticles. The structural formula of the PP5-1F is as follows:

[0008]

[0009] The present invention also provides a method for preparing the PP5-1F-MNP, comprising the following steps:

[0010] (1) Preparation of 1,4-bis(2-bromoethoxy)benzene

[0011] Under the condition of an ice-water bath at 0°C, hydroquinone dihydroxyethyl ether and triphenylphosphine are added to anhydrous acetonitrile, and then carbon tetrabromide is slowly added under the protection of an inert gas (preferably nitrogen), and then the reaction system is restored to room temperature, and stirred at room temperature until the solution is clear and transparent (preferably the stirring time is 3-6 hours), and then cold water is added to quench the reaction, and the product is purified (preferably recrystallized from methanol) and dried (preferably vacuum dried at 40°C for 24 hours) to obtain 1,4-bis(2-bromoethoxy)benzene;

[0012] (2) Preparation of brominated functional group column [5] aromatic hydrocarbons

[0013] Add paraformaldehyde to a solution of 1,4-bis(2-bromoethoxy)benzene (preferably a solution of 1,4-bis(2-bromoethoxy)benzene in dichloroethane or dichloromethane), then add boron trifluoride etherate (BF3·O(C2H5)2), stir at room temperature for 4-8 hours, and after the reaction is completed, quench the reaction with cold water, purify and dry the product to obtain brominated functional group column [5] aromatic hydrocarbons;

[0014] (3)PP5-1F

[0015] Add the brominated functional group column [5] aromatic hydrocarbon to 3-fluoropyridine, heat the reaction mixture under reflux and stir for 8-12 hours, and after the reaction is completed, obtain a yellow solid, purify (preferably by recrystallization from ether), and dry to obtain PP5-1F (preferably by vacuum drying at 40°C for 24 hours);

[0016] (4)PP5-1F-MNP

[0017] PP5-1F was added to ethylene glycol and dissolved by ultrasonication. FeCl3·6H2O and sodium acetate were then added. After ultrasonic dispersion, the mixture was stirred evenly at room temperature. The mixture was then transferred to a polytetrafluoroethylene reactor and reacted at 100-250°C for 8-12h (preferably at 200°C for 10h). The mixture was washed and dried to obtain a black magnetic column [5] aromatic polymer PP5-1F-MNP.

[0018] Preferably, in said (4), anhydrous ethanol and deionized water are used for alternate washing, and said drying is: vacuum drying at 40° C. for 24 hours.

[0019] Preferably, in step (1), the molar ratio of hydroquinone dihydroxyethyl ether to triphenylphosphine is 1:(2-3), and the molar ratio of triphenylphosphine to carbon tetrabromide is 1:1. Optimally, the molar ratio of hydroquinone dihydroxyethyl ether, triphenylphosphine and carbon tetrabromide is 5:12:12.

[0020] Preferably, in step (2), the molar ratio of 1,4-bis(2-bromoethoxy)benzene, paraformaldehyde and boron trifluoride etherate is 1:(0.5-3):(0.5-1.5), most preferably 1:1:1.

[0021] Preferably, in step (3), the ratio of column [5] aromatic hydrocarbon to 3-fluoropyridine is 0.3-1.2 mmol: 5-10 mL.

[0022] Preferably, in step (4), the molar ratio of PP5-1F to FeCl3·6H2O and sodium acetate is (0.05-0.5):1:(2-8), and most preferably 0.15:1:4.

[0023] Preferably, in step (4), the ratio of PP5-1F to ethylene glycol is 0.5-2 g: 10-30 mL.

[0024] The present invention also provides a method for detecting the content of PFCs based on magnetic solid phase extraction-high performance liquid chromatography tandem mass spectrometry of the PP5-1F-MNP:

[0025] (1) Chromatographic conditions

[0026] Chromatographic column: C18 column;

[0027] Mobile phase A: 5mmol / L ammonium acetate aqueous solution, mobile phase B: acetonitrile;

[0028] Flow rate: 0.4 mL / min;

[0029] Column temperature: 40°C;

[0030] Gradient elution conditions:

[0031] Time (min) Mobile phase A (v / v%) Mobile phase B (v / v%) 0-1 90 10 1-5 90-10 10-90 5-8 10 90 8-10 10-90 90-10

[0032] (2) Mass spectrometry conditions

[0033] Electrospray ionization (ESI) source was used to ionize in negative ion mode, and multiple reaction monitoring mode (MRM) was established to analyze PFCs; nebulizer gas flow rate: 3 L / min, heating gas flow rate: 10 L / min, drying gas flow rate: 10 L / min, interface temperature: 300 °C, DL temperature: 250 °C, heating block temperature: 400 °C, and each MRM dwell time was 12 ms;

[0034] (3) Magnetic solid phase extraction step

[0035] After mixing PP5-1F-MNP with the PFCs sample solution to be tested, vortex operation is performed on a vortex mixer for 2-15 minutes (preferably 5 minutes) to ensure that the PP5-1F-MNP adsorbent fully and selectively adsorbs PFCs. The external magnet quickly separates the PP5-1F-MNP adsorbent from the solution effectively, washes PP5-1F-MNP with pure water to remove PFCs not adsorbed on the surface, adds a desorption solution (preferably dichloromethane, ethyl acetate, acetone, methanol or acetonitrile, most preferably acetonitrile), and vortexes for 3-15 minutes (preferably 8 minutes) to desorb the PFCs adsorbed by PP5-1F-MNP. After separating PP5-1F-MNP from the solution, a certain amount of solution is taken, concentrated to dryness, and then the desorption solution is added to redissolve the PFCs. The re-dissolved solution is taken for HPLC-MS / MS detection.

[0036] Preferably, the dosage ratio of the PP5-1F-MNP adsorbent to the desorption liquid is (5-20) mg: (3-13) mL; more preferably 15 mg: 7 mL.

[0037] Preferably, the dosage ratio of the PP5-1F-MNP adsorbent to the sample solution is (5-20) mg: (3-13) mL; more preferably 15 mg: 10 mL.

[0038] Preferably, when the reconstituted solution is subjected to HPLC-MS / MS detection, the content of PFCs is detected using the internal standard method. 13 C8-PFOA and 13 C8-PFOS was used as an internal standard.

[0039] Preferably, the PFCs are long-chain PFCs with a carbon chain of not less than 8, more preferably C8-C 14 Long chain PFCs, most preferably C8-C 14 Perfluorocarboxylic acids and / or perfluorosulfonic acids.

[0040] The present invention uses PP5-1F-MNP as a magnetic solid phase extraction adsorbent to explore the adsorption effect of PFCs, and finds that PP5-1F-MNP has an adsorption effect on 8 long-chain PFCs. The MSPE conditions are optimized, and a PP5-1F-MNP-MSPE HPLC-MS / MS method for detecting 8 PFCs is established, and the method is used for the quantitative analysis of PFCs in water samples from Nanhu Lake, Donghu Lake, Thomson Lake and rainwater samples in Wuhan.

[0041] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0042] 1. The present invention is the first to react bromine functional group column [5] aromatic hydrocarbons with 3-fluoropyridine to generate cationic column [5] aromatic hydrocarbons (PP5-1F) for C8-C 14 It has excellent adsorption performance for long-chain PFCs, and its adsorption recovery rate can reach more than 70%. The maximum adsorption capacities for perfluorooctanoic acid (PFOA), perfluorosulfonic acid (PFOS) and perfluoroundecanoic acid (PFUnDA) are 42.02, 62.11 and 64.94 mg / g, respectively.

[0043] 2. The magnetic adsorbent of the present invention has a simple preparation process, low cost, and ideal adsorption effect. After adsorption, it is easy to be effectively separated from the system and can be recycled, so it is suitable for industrial production.

[0044] 3. The present invention constructs a new method of magnetic solid phase extraction assisted high performance liquid chromatography-tandem mass spectrometry, which can simultaneously perform quantitative analysis on 8 kinds of PFCs. For 8 kinds of long-chain PFCs, the linear range of this method is in the range of 2.0ng / L to 100ng / L. Correlation coefficient R 2Greater than 0.9964. The range of LOD is 1.0-2.8 ng / L, the range of LOQ is 2.0-10.0 ng / mL, and the range of RSD is 1.7-6.3%. It can be used for the detection of PFCs in actual water samples such as lake water and rainwater. The spiked recoveries are between 84.8% and 104.7%, and the RSD is in the range of 0.61-13.1%. The established method has good linearity, high recovery, low detection limit, high sensitivity, good reproducibility, etc., which is of great significance for accurately assessing its environmental exposure level and health risks. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of column [5] aromatic hydrocarbon in Example 1;

[0046] Figure 2 is the carbon NMR spectrum of column [5] aromatic hydrocarbon in Example 1;

[0047] Figure 3 is the hydrogen nuclear magnetic resonance spectrum of the cationic column [5] aromatic hydrocarbon (PP5-1F) in Example 1;

[0048] Figure 4 is the carbon NMR spectrum of the cationic column [5] aromatic hydrocarbon (PP5-1F) in Example 1;

[0049] Figure 5 is the infrared spectra of PP5-1F and PP5-1F-MNP in Example 1;

[0050] Figure 6 (A) and (B) are field emission scanning electron micrographs of Fe3O4 nanoparticles with scale bars of 2 μm and 800 nm, respectively; (C) and (D) are field emission scanning electron micrographs of PP5-1F-MNPs with scale bars of 2 μm and 800 nm, respectively;

[0051] Figure 7 (A) and (B) are transmission electron micrographs of Fe3O4 nanoparticles with a scale of 500 nm and 200 nm, and (C) and (D) are transmission electron micrographs of PP5-1F-MNPs with a scale of 2 μm and 200 nm;

[0052] Figure 8 is the nitrogen adsorption-desorption isotherm and pore size distribution diagram of PP5-1F-MNP in Example 1;

[0053] Fig. 9 is a hysteresis loop curve diagram of Fe3O4 nanoparticles and PP5-1F-MNP in Example 1;

[0054] Fig.10is the water contact angle diagram of Fe3O4 nanoparticles and PP5-1F-MNP in Example 1;

[0055] Fig.11 is a graph showing the results of adsorbent quality optimization in Example 2;

[0056] Fig.12 This is a diagram showing the optimization results of adsorption time in Example 2;

[0057] Fig.13 is a diagram showing the optimization results of the desorption liquid type in Example 2;

[0058] Fig.14 is a graph showing the optimization results of the desorption liquid volume in Example 2;

[0059] Fig.15 It is the desorption time optimization result diagram in Example 2;

[0060] Fig.16 is the adsorption isotherm diagram of PP5-1F-MNP for three PFCs in Example 2;

[0061] Fig.17 is the chromatogram of the mixed standard of 8 PFCs and two isotopic internal standards in Example 2;

[0062] Fig.18 This is a full scan of the eight PFCs and two isotope internal standards in Example 2 in negative ion mode. DETAILED DESCRIPTION

[0063] The applicant will explain the technical solution of the present invention in detail below in conjunction with specific examples, but it should be understood that the following examples are only used to illustrate the present invention, and are not used to limit the scope of protection claimed in the claims of the present invention. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can all be obtained from commercial channels.

[0064] The information of PFCs standards and some reagents used in the following examples are shown in Table 1 below:

[0065] Table 1

[0066] Reagent name Reagent Specifications Manufacturer Perfluorobutyric acid (PFBA) ≥98% Aladdin Reagent Co., Ltd. Perfluorobutane sulfonic acid (PFBS) ≥98% BiDe Pharmaceutical Technology Co., Ltd. Perfluorohexanoic acid (PFHxA) ≥97% Sigma Reagents Ltd. Perfluoropentanoic acid (PFPeA) ≥97% Bailingwei Technology Co., Ltd. Perfluoroheptanoic acid (PFHpA) ≥99% BiDe Pharmaceutical Technology Co., Ltd. Perfluorooctanoic acid (PFOA) ≥96% Sigma Reagents Ltd. Perfluorooctane sulfonic acid (PFOS) 100 μg / mL Bailingwei Technology Co., Ltd. Perfluorononanoic acid (PFNA) ≥98% Bailingwei Technology Co., Ltd. Perfluorodecanoic acid (PFDA) ≥98.0% Aladdin Reagent Co., Ltd. Perfluoroundecanoic acid (PFUnDA) ≥97.0% Aladdin Reagent Co., Ltd. Perfluorododecanoic acid (PFDoDA) ≥95.0% Aladdin Reagent Co., Ltd. Perfluorotridecanoic acid (PFTrDA) ≥97% Sigma Reagents Ltd. Perfluorotetradecanoic acid (PFTeDA) ≥96% Bailingwei Technology Co., Ltd. <![CDATA[ 13 C8-Perfluorooctanecarboxylic acid ( 13 C8-PFOA)]]> ≥99% Wellington Laboratory, Canada <![CDATA[ 13 C8-Perfluorooctanesulfonic acid ( 13 C8-PFOS)]]> ≥99% Wellington Laboratory, Canada Methanol Chromatographic pure Merk Reagent Company, Germany Acetonitrile Chromatographic pure Merk Reagent Company, Germany acetone Chromatographic pure Thermo Fisher Scientific 1,2-Dichloromethane Chromatographic pure Thermo Fisher Scientific n-Hexane Chromatographic pure Aladdin Reagent Co., Ltd. Ammonium acetate Chromatographic pure Sinopharm Chemical Reagent Co., Ltd. Yibao purified water ― China Resources C'estbon Beverages (Changsha) Co., Ltd. Paraformaldehyde (Cat. No.: C104188) AR Aladdin Reagent Co., Ltd.

[0067] Example 1: Preparation and characterization of magnetic cation column [5] aromatic porous polymer

[0068]

[0069] A method for preparing a magnetic column [5] aromatic hydrocarbon porous polymer BrBP [5] -MNP comprises the following steps:

[0070] (1) Preparation of 1,4-bis(2-bromoethoxy)benzene

[0071] Under the condition of 0℃ ice-water bath, 50.4mmol hydroquinone dihydroxyethyl ether and 120mmol triphenylphosphine (PPh3) were added to 300mL acetonitrile, and then 120mmol carbon tetrabromide (CBr4) was slowly added under nitrogen protection, the ice bath was removed, and the reaction system was restored to room temperature (room temperature in this application refers to 25℃), and stirred at room temperature for 4h until the solution was clear and transparent. Then, an appropriate amount of cold water (ultrapure water at room temperature, the same below) was added to the reaction mixture to quench the reaction. Filter, collect the solid, wash with methanol / water (60:40, v / v), and obtain the product as a white flaky solid, and finally vacuum dry at 40℃ for 24h to obtain 1,4-bis(2-bromoethoxy)benzene with a yield of 85%.

[0072] (2) Preparation of brominated functional group column [5] aromatic hydrocarbons

[0073] 11.5mmol of paraformaldehyde (in this application, the molecular weight of paraformaldehyde is 30.03) was added to a solution of 1,4-bis(2-bromoethoxy)benzene (11.5mmol) in 1,2-dichloroethane (200mL). Subsequently, 11.5mmol of BF3·O(C2H5)2 was added and stirred at room temperature for 6h. The reaction progress was monitored by thin layer chromatography. After the reaction was completed, it was quenched with (2×100mL) of cold water. After extraction with a saturated dichloromethane solution of sodium chloride, the organic phase was dried over anhydrous Na2SO4, concentrated under reduced pressure, purified by silica gel column chromatography (eluent: petroleum ether / dichloromethane = 1:1, v / v), and finally dried in vacuum at 40°C for 24h to obtain a white powder of brominated functional group column [5] aromatic hydrocarbon. The yield of this step was 41%.

[0074] (3) Preparation of PP5-1F

[0075] 0.3 mmol of column [5] aromatic hydrocarbon was added to 5 mL of anhydrous 3-fluoropyridine, and the reaction mixture was heated to reflux and stirred for 10 h. After the reaction was completed, a yellow solid was obtained. After recrystallization with ether, it was vacuum dried at 40 ° C for 24 h to obtain PP5-1F. The yield of this step was 90%.

[0076] (4) Preparation of PP5-1F-MNPs

[0077] 0.3 mmol PP5-1F was added to 20 mL anhydrous ethylene glycol, and after ultrasonic dissolution, 2 mmol FeCl3·6H2O and 8 mmol sodium acetate were added, and after ultrasonic dispersion, the mixture was stirred at room temperature for 30 min. Then the mixture was transferred to a 100 mL polytetrafluoroethylene reactor, reacted at 200 ° C for 10 h, and then cooled to room temperature. Under the action of an external magnetic field, the mixture was washed alternately with ethanol and deionized water for 5 times each. After washing, the mixture was filtered and the filter cake was dried in a vacuum oven at 40 ° C for 24 h to obtain a black magnetic column [5] aromatic polymer PP5-1F-MNP. The yield of this step was 60%.

[0078] (5) Preparation of Fe3O4 nanoparticles

[0079] 20mmol FeCl3·6H2O was added to a three-necked flask containing 100mL ethylene glycol, and after ultrasonic dispersion for 20min, 80mmol sodium acetate was added and mechanically stirred at room temperature for 30min. The uniform yellow solution was transferred to a polytetrafluoroethylene reactor, sealed and reacted at 200℃ for 10h, then cooled to room temperature, and washed alternately with ethanol and deionized water under the action of an external magnetic field, each for 5 times. After washing, the black product was placed in a vacuum drying oven at 25℃ and dried for 12h to obtain Fe3O4 nanoparticles.

[0080] The PP5-1F, PP5-1F-MNP and Fe3O4 nanoparticles prepared in this example were characterized, and the results were as follows:

[0081] (1) NMR analysis

[0082] The present invention uses the AVANCE III nuclear magnetic resonance spectrometer of Bruker BioSpin Company of Switzerland to perform structural analysis on column [5] aromatic hydrocarbons and PP5-1F. The solvent of column [5] aromatic hydrocarbons is deuterated chloroform, and its H spectrum and C spectrum are as follows: Figure 1 , 2 As shown, the solvent of PP5-1F is deuterated methanol, and its H spectrum and C spectrum are as follows Figure 3 , 4 shown.

[0083] (2) Fourier transform infrared spectroscopy (FT-IR)

[0084] The present invention uses the NEXUS 470 infrared spectrometer of Niolet Company in the United States. The instrument model is Nexus470 to characterize the characteristic functional groups of PP5-1F and PP5-1F-MNP. Potassium bromide is used as the substrate for tableting test to obtain the infrared spectrum data of the sample. The test wavelength range is 4000-500cm -1 , the results are as follows Figure 5 shown. Figure 5PP5-1F at 1503cm -1 , 1593cm -1 The peak at 1590 cm-1 of PP5-1F-MNP -1 The peak at 1285cm is the stretching vibration peak of the benzene ring skeleton; PP5-1F at 1285cm -1 and PP5-1F-MNP at 1349 cm -1 The peak at 578 cm-1 is the stretching vibration peak of the CF bond on the benzene ring, indicating that the reaction between column[5]arene and 3-fluoropyridine was successful, confirming the existence of the CF bond in the material. -1 The peak at is the stretching vibration peak of the Fe-O bond, indicating that the magnetization of PP5-1F was successfully formed. The characteristic peaks of the Fe-O bond and the CF bond in the spectrum indicate that PP5-1F was successfully modified with magnetic nanoparticles.

[0085] (3) Field emission scanning electron microscopy (SEM)

[0086] The present invention uses a field emission scanning electron microscope (model SU8010) produced by Japan HITACHI Company to conduct a preliminary analysis of the size and morphology of the synthetic material. The operation process is as follows: Fe3O4 nanoparticles and PP5-1F-MNP powder are uniformly adhered to the sample stage with conductive glue. The size and morphology of the material can be observed through the electron microscope. Figure 6 (A) and (B) show the SEM images of Fe3O4 nanoparticles with a scale of 2μm and 800nm ​​respectively. It can be clearly seen from the figure that Fe3O4 presents a spherical shape with uniform size and good dispersion. Figure 6 (C) and (D) in the figure show SEM images of PP5-1F-MNP with a scale of 2μm and 800nm. It can be observed from the figure that PP5-1F-MNP has an irregular morphology. Compared with (A) and (B), it can be seen that in PP5-1F-MNP, part of Fe3O4 is successfully encapsulated inside, but part of it is not fully encapsulated, showing a rough and uneven surface of Fe3O4. It is speculated that this may be caused by excessive Fe3O4 and easy agglomeration during the reaction process.

[0087] (4) Transmission Scanning Electron Microscope (TEM)

[0088] The morphology of Fe3O4 nanoparticles and PP5-1F-MNPs was further characterized using a TALOS F200X transmission electron microscope from Thermo Fisher Scientific, USA. The material samples were ground and ultrasonically dispersed on a copper mesh with anhydrous ethanol, and then tested after the ethanol evaporated. Figure 7(A) and (B) show TEM images of Fe3O4 nanoparticles with a scale of 500nm and 200nm, respectively. It can be seen from the figures that each Fe3O4 nanoparticle has a clear spherical outline, a smooth surface and uniform size. Figure 7 (C) and (D) show the TEM images of PP5-1F-MNP with a scale of 2 μm and 200 nm, respectively. It can be seen from the figures that the Fe3O4 nanoparticles are encapsulated inside and their surface is covered with a transparent shell structure, which is consistent with the results of scanning electron microscopy.

[0089] (5) Nitrogen physical adsorption and desorption

[0090] The present invention uses a nitrogen adsorption-desorption instrument produced by Mack, USA, the instrument model is ASAP 2020, to characterize the pore structure information such as pore size and specific surface area of ​​PP5-1F-MNP. The operation process is as follows: N2 adsorption and desorption experiments are carried out at 77k, and the specific surface area and pore size of PP5-1F-MNP are calculated using the BET method and the Barrett-Joyner-Halenda (BJH) model. Figure 8 From the adsorption-desorption isotherm in (A), we can see that the adsorption and desorption behavior of PP5-1F-MNP conforms to the H1 loop characteristics of the typical IV type isotherm. This phenomenon shows that there is an obvious hysteresis phenomenon in the adsorption and desorption process, indicating the existence of mesoporous structure in the material. Figure 8 As can be seen from (B), the specific surface area of ​​PP5-1F-MNP calculated using the BJH model is 89.05 m 2 / g, and the average pore size is 19.28nm, which fully proves that PP5-1F-MNP is a material with mesoporous characteristics.

[0091] (6) Hysteresis loop analysis (VSM)

[0092] The saturation magnetization values ​​of Fe3O4 nanoparticles and PP5-1F-MNP were measured using a 7074 model vibrating sample magnetometer from Lake Shore, USA, to fully evaluate their magnetization properties. Fig. 9 The hysteresis loop curves of Fe3O4 and PP5-1F-MNP show that the saturation magnetization value of Fe3O4 nanoparticles is 45.0emu / g, and the saturation magnetization value of PP5-1F-MNP is 12.7emu / g. Compared with Fe3O4, the magnetization value decreases, indicating that the magnetization value of Fe3O4 will decrease after being successfully coated by PP5-1F, but PP5-1F-MNP still has strong paramagnetism, and the material can be quickly separated from the solution by an external magnetic field in a short time, thereby improving the adsorption efficiency.

[0093] (7) Water contact angle analysis (CA)

[0094] The present invention uses the OCA20 water contact angle analyzer of Dataphysics of Germany to test the hydrophilicity and hydrophobicity of the synthetic material. The operation process is as follows: weigh appropriate amounts of Fe3O4 and PP5-1F-MNP materials and press them into disc-shaped sheets, drop water on the surface of the material, and measure the angle between the water drop and the surface of the material. Fig.10 The water contact angles of Fe3O4 nanoparticles and PP5-1F-MNPs. It can be seen from the figure that the water contact angle of Fe3O4 is 94.9°, and the water contact angle of PP5-1F-MNP is 56.2°. After the successful magnetization of PP5-1F-MNP, the water contact angle decreases, which means that PP5-1F-MNP has hydrophilicity and can better contact with aqueous solutions.

[0095] Example 2: Investigation of magnetic solid phase extraction assisted high performance liquid chromatography-tandem mass spectrometry method based on PP5-1F-MNP

[0096] Chromatographic conditions:

[0097] Chromatographic column: Waters ACQUITY UPLC C18 column (1.7 μm, 2.1×100 mm);

[0098] Mobile phase A: 5mmol / L ammonium acetate aqueous solution; Mobile phase B: acetonitrile;

[0099] Flow rate: 0.4 mL / min; column temperature: 40 °C;

[0100] Gradient elution conditions:

[0101] Time (min) Mobile phase A (v / v%) Mobile phase B (v / v%) 0-1 90 10 1-5 90-10 10-90 5-8 10 90 8-10 10-90 90-10

[0102] Mass spectrometry conditions:

[0103] High performance liquid chromatography-tandem mass spectrometry (HPLC-MS-8050) electrospray ionization (ESI) produced by Shimadzu, Japan was used. The mass spectrometry parameters were: nebulizing gas flow rate: 3 L / min, heating gas flow rate: 10 L / min, drying gas flow rate: 10 L / min, interface temperature: 300°C, DL temperature: 250°C, heating block temperature: 400°C, and each MRM residence time was 12 ms.

[0104] First, in the negative ion mode, a full scan was performed on the 13 PFCs standards and 2 internal standards shown in Table 2 to determine the precursor ions. Secondly, multiple fragmentation voltages were set in combination with the found precursor ions, and the corresponding fragmentation voltages were obtained by product ion scanning. According to the abundance of the fragment ions, the one with the largest abundance was selected as the quantitative ion, and the one with the second largest abundance was selected as the qualitative ion, and the parent-daughter ion pairs corresponding to the 15 substances were obtained. Finally, based on the determined parent-daughter ion pairs, the collision energy was optimized, the instrument parameters in MS and MS / MS were optimized as a whole, and a multiple reaction monitoring mode method (MRM) was established. The optimized MRM analysis parameters for the 13 PFCs and two isotopic internal standards are shown in Table 2:

[0105] Table 2: Mass spectrometry parameters of 13 PFCs and two isotopic internal standards

[0106]

[0107] 1. Study on adsorption effect

[0108] Preparation of standard stock solutions: Weigh 10 mg of 13 PFCs standards respectively and dissolve them in 10 mL of chromatography grade acetonitrile to prepare 1 mg / mL standard stock solutions, which are then stored in a refrigerator at 4°C.

[0109] 0.1 ng / mL PFCs mixed standard solution: Take 50 μL of 1 mg / mL standard stock solutions of 13 PFCs respectively, mix them, add 350 μL acetonitrile to dilute them into 50 μg / mL mixed standard solution, and then dilute the 50 μg / mL mixed standard solution with acetonitrile to 0.1 ng / mL mixed standard solution.

[0110] Prepare standard internal standard solution: 13 C8-PFOA and 13 The two compounds C8-PFOS were used as internal standard substances, and were dissolved in chromatography grade acetonitrile to prepare solutions with a concentration of 50 μg / mL, which were stored in a refrigerator at 4°C.

[0111] 10ng / mL internal standard mixed solution: take 50μg / mL 13 C8-PFOA and 13 200 μL of each C8-PFOS solution was mixed and 600 μL of acetonitrile was added to dilute it to a 10 μg / mL internal standard mixed solution, and then the 10 μg / mL internal standard mixed solution was diluted with acetonitrile to a 10 ng / mL internal standard mixed solution.

[0112] Prepare standard curve: accurately pipette the above 50 μg / mL mixed standard solution, dilute it with HPLC grade acetonitrile, and prepare a series of mixed standard solutions with concentrations of 0.01 ng / mL, 0.02 ng / mL, 0.05 ng / mL, 0.1 ng / mL, 0.2 ng / mL, 0.5 ng / mL, 1 ng / mL, 2 ng / mL, 5 ng / mL, 10 ng / mL, 20 ng / mL, 50 ng / mL, and 100 ng / mL, respectively. Centrifuge for 3 minutes, take 90 μL of supernatant and add 10 μL of internal standard mixed solution with a concentration of 10 ng / mL ( 13 C-PFOA and 13 C-PFOS), vortexed and mixed, centrifuged for 3 minutes, 70 μL was taken into the injection bottle, and the HPLC-MS / MS was directly injected with an injection volume of 5 μL. Each variable was measured three times in parallel. The concentration of each compound was used as the horizontal axis (X), and the peak area of ​​each compound was compared with the corresponding internal standard (the internal standard of perfluorocarboxylic acid is 13 C8-PFOA, the internal standard for perfluorosulfonic acid is 13 The standard curve was drawn with the peak area ratio of C8-PFOS (the same below) as the ordinate (Y).

[0113] PP5-1F-MNP was used as a magnetic solid phase extraction adsorbent to conduct an adsorption-desorption experiment on PFCs. The specific steps are as follows:

[0114] 10 mg of the PP5-1F-MNP adsorbent obtained in Example 1 was placed in a 50 mL centrifuge tube, and 10 mL of a mixed standard solution of 13 PFCs with a concentration of 0.1 ng / mL was added, and the vortex operation was performed on a vortex mixer for 5 minutes to ensure that the PP5-1F-MNP adsorbent fully and selectively adsorbed the PFCs. The external magnet quickly separated the PP5-1F-MNP adsorbent from the solution, and then 5 mL of pure water was added to elute the PFCs that were not adsorbed on the surface of the PP5-1F-MNP adsorbent, and the solid adsorbent was separated from the solution by a magnet again. 5 mL of acetonitrile was added as a desorption liquid, and vortexed for 5 minutes to desorb the PFCs adsorbed by the PP5-1F-MNP. The magnet was attached to the outside of the centrifuge tube to adsorb the material, and it was allowed to stand for clarification. 4 mL of the supernatant was taken and blown dry using a nitrogen blower. 200 μL of chromatography-grade acetonitrile was added to re-dissolve the PFCs. The re-dissolved solution was centrifuged for 3 min, and then 90 μL of the supernatant was taken and 10 μL of 10 ng / mL of 13 C8-PFOA and 13 After the C8-PFOS internal standard mixed solution is mixed evenly, 70 μL is taken for HPLC-MS / MS mass spectrometry detection, the mass spectrometry injection volume is 5 μL, and the parallel determination is performed three times.

[0115] Calculate the ratio of the peak area of ​​perfluorocarboxylic acid or perfluorosulfonic acid to its corresponding internal standard, substitute it into the above standard curve equation, and obtain the actual sample concentration.

[0116] Recovery rate calculation: Recovery rate (%) = actual sample concentration / theoretical calculated concentration × 100%, where the theoretical calculated concentration is the concentration of the known standard solution.

[0117] The recovery rate of 13 PFCs after adsorption by PP5-1F-MNP was analyzed. The results showed that PP5-1F-MNP material had a certain adsorption capacity for 8 long-chain PFCs, namely PFOA, PFOS, PFNA, PFDA, PFUnDA, PFDoDA, PFTrDA and PFTeDA. The adsorption effect of PP5-1F-MNP material on the above 8 long-chain PFCs was better than that on short-chain PFCs (PFBS, PFBA, PFPeA, PFHxA, PFHpA). The main reasons may be: First, PP5-1F-MNP is a magnetic cationic column [5] aromatic polymer, which can effectively adsorb PFCs through electrostatic force. With the increase of carbon chain length, the pKa values ​​of 13 PFCs gradually decreased, indicating that their acidity increased. In neutral or weakly alkaline solutions, these PFCs will lose protons and exist in anionic state, which makes PP5-1F-MNP have a higher adsorption capacity for long-chain PFCs. Secondly, the PP5-1F-MNP material contains F atoms, which can adsorb PFCs through FF interactions. As the carbon chain increases, the number of F atoms in PFCs increases, the FF interaction is enhanced, and the adsorption effect is enhanced. Therefore, PP5-1F-MNP has a relatively good adsorption effect on long-chain PFCs. Finally, the PP5-1F-MNP material contains a rigid cavity structure. PFCs of different sizes can selectively enter the cavity of the PP5-1F-MNP material through host-guest interactions. The molecular size of long-chain PFCs is larger than that of short-chain PFCs. Long-chain PFCs are less likely to come out of the cavity of the PP5-1F-MNP material, so the adsorption effect of long-chain PFCs is better. The experimental results show that PP5-1F-MNP has the ability to selectively adsorb C8 to C 14 The ability of PP5-1F-MNP to absorb the long-chain PFCs and show significant adsorption effect. Therefore, PP5-1F-MNP has the potential to be used as an adsorbent material for magnetic solid phase extraction. Subsequent experiments will explore the adsorption conditions of PP5-1F-MNP material for the above eight long-chain PFCs to determine its optimal adsorption performance.

[0118] 2. Optimization of adsorption-desorption conditions (8 long-chain PFCs)

[0119] In order to optimize the adsorption and desorption conditions, a single-factor experimental design was used. The experiment was mainly carried out around the following key factors: adsorbent dosage, adsorption time, desorption liquid type, desorption liquid volume and desorption time. To ensure the accuracy and reliability of the experimental results, three parallel experiments were conducted for each variable. In-depth exploration of the adsorption performance of PP5-1F-MNP adsorbent on PFCs in order to achieve the best adsorption effect.

[0120] Preparation of mixed standard solutions of 8 PFCs: Take 50 μL of 1 mg / mL standard stock solutions of PFOA, PFOS, PFNA, PFDA, PFUnDA, PFDoDA, PFTrDA and PFTeDA, mix them, add 600 μL of acetonitrile to dilute them into 50 μg / mL mixed standard solutions, and then dilute the 50 μg / mL mixed standard solutions with acetonitrile to 0.1 ng / mL mixed standard solutions.

[0121] Adsorbent dosage: First, the effect of the quality of PP5-1F-MNP adsorbent on the adsorption of PFCs was studied. 5 mg, 8 mg, 10 mg, 15 mg, 20 mg and 25 mg of PP5-1F-MNP material were accurately added to 6 50 mL centrifuge tubes. Then, 10 mL of a mixed standard solution of 8 PFCs with a concentration of 0.1 ng / mL was added to each centrifuge tube. The specific steps of the experiment were carried out according to the adsorption-desorption experiment in 1. The results are shown in the figure. Fig.11 , the results show that: in the early stage, as the mass of the adsorbent increases, the recovery rate of PFCs also increases, and the optimal extraction recovery rate is reached at 15 mg. This may be because after the mass of PP5-1F-MNP increases, its specific surface area also increases accordingly, and the adsorption sites on the surface of the material also increase accordingly, and the adsorption process mainly occurs on the surface of the adsorbent, so the recovery efficiency is improved. Secondly, the increase in the mass of the adsorbent means the increase in its total adsorption capacity, which can better remove PFCs in the solution. However, the increase in the mass of the adsorbent does not always linearly improve the adsorption effect, because when the adsorbent reaches a certain amount, the adsorption effect may tend to saturation. Considering the economic benefit issue, 15 mg of PP5-1F-MNP material was finally selected as the optimal adsorbent dosage for subsequent experimental research.

[0122] Adsorption time: The adsorption process is a dynamic equilibrium process, and the adsorption time is also one of the important factors affecting the adsorption effect of the material. It is necessary to optimize the adsorption time and change the adsorption time. The adsorption was performed for 2min, 5min, 8min, 10min, 12min, and 15min respectively. The amount of adsorbent was 15mg, and the rest of the experimental process was carried out according to 1. The results are as follows Fig.12As shown in the figure, the adsorption recovery rate of the eight PFCs increases with the increase of adsorption time when the adsorption time is short, decreases slightly after the adsorption reaches 10 minutes, and finally tends to be flat. Since adsorption-desorption is a complex dynamic equilibrium process, its characteristic is that PFCs reach a stable distribution state on the adsorbent surface and in the solution. At this time, no matter how the adsorption time increases, the recovery rate will no longer be significantly improved. Therefore, in order to ensure the adsorption effect while improving the efficiency and avoid the waste of resources and reduced efficiency caused by too long adsorption time, 5 minutes was finally selected as the optimal adsorption time of PP5-1F-MNP material for the next step of optimization.

[0123] Type of desorption liquid: Different solvents have different desorption capacities for PFCs. In order to improve the adsorption efficiency of PP5-1F-MNP for PFCs, it is particularly important to select a suitable desorption solvent. Based on the above optimized conditions, six desorption liquids with different polarities were selected for optimization. The six desorption liquids were n-hexane, dichloromethane, ethyl acetate, acetone, methanol and acetonitrile. The results are shown in Figure 2. Fig.13 As shown, n-hexane has almost no elution effect on the eight PFCs, and the recovery rate is less than 10%. The other five organic solvents with different polarity also have different elution effects on PFCs. Among them, when acetonitrile is used as the desorption liquid, the recovery rate of the eight PFCs is the highest. It may be due to the strong elution ability and polarity of acetonitrile, which can effectively interact with PFCs and destroy the electrostatic force between the adsorbent and PFCs, thereby achieving desorption. Therefore, acetonitrile was selected as the optimal desorption liquid to explore the subsequent conditions.

[0124] Desorption liquid volume: The desorption process is a kinetic process, and changes in the desorption liquid volume will affect the desorption rate. A larger desorption liquid volume may accelerate the desorption rate because it can remove the desorbed PFCs from the PP5-1F-MNP adsorbent surface more quickly, thereby reducing the possibility of re-adsorption of the desorbed PFCs. However, in order to ensure that the extraction recovery rate is maximized while avoiding unnecessary solvent waste, the amount of desorption liquid is optimized. According to the adsorption-desorption experiment in 1, on the basis of the above optimal conditions, 3mL, 5mL, 7mL, 9mL, 11mL, and 13mL of chromatographic grade acetonitrile were added during elution, respectively. The results are as follows. Fig.14 As shown, the adsorption effect of PFCs is relatively good when the desorption liquid volume is 7 mL. Among them, PFOA, PFOS, PFUnDA and PFDoDA have the highest adsorption recovery rate when the desorption liquid volume is 7 mL, and other compounds do not change much, so 7 mL is selected as the optimal desorption liquid volume.

[0125] Desorption time: Desorption time is also one of the important factors affecting adsorption efficiency. It is necessary to optimize the desorption time according to the specific adsorption system and target to achieve the best adsorption efficiency. According to the adsorption-desorption experiment in 1, on the basis of the above optimal conditions, vortex elution was performed for 3min, 5min, 8min, 10min, 12min and 15min respectively. The results are as follows Fig.15 As shown in the figure, for most PFCs, when the vortex elution time is 3-8min, the adsorption efficiency of PFCs increases slightly with the increase of desorption time, and the adsorption efficiency is the highest at 8min. At 10-15min, the adsorption efficiency of PFCs decreases with the increase of desorption time. This may be because when the concentration of PFCs decreases or there are other competitive adsorbents, the adsorbed molecules may desorb from the adsorbent, resulting in a decrease in the adsorption amount. Therefore, 8min is selected as the optimal desorption time.

[0126] In summary, the optimal conditions for PP5-1F-MNP as a magnetic solid phase extraction adsorbent are: 15 mg of PP5-1F-MNP adsorbent, 5 min of adsorption time, acetonitrile as desorption liquid, 7 mL of desorption liquid, and 8 min of desorption time. After optimizing the adsorption-desorption conditions, the efficient extraction of 8 long-chain PFCs was successfully achieved, and significant extraction effects were achieved.

[0127] 3. Adsorption isotherm experiment

[0128] In order to fully understand the adsorption characteristics of PP5-1F-MNP for PFCs, reveal the interaction mechanism between PP5-1F-MNP and PFCs, and accurately evaluate its adsorption capacity for PFCs, three PFCs substances were selected as research objects for adsorption isotherm experiments, namely PFOA, PFOS and PFUnDA. PFOS and PFOA, as the main representative substances of PFCs, are widely present in the environment. Currently, the Stockholm Convention and its related compounds have been included in the list of controlled substances to restrict their global use. PFUnDA, as a representative of long-chain PFCs, is difficult to degrade due to its stability and environmental persistence, and is widely present in environmental media. Exploring the adsorption behavior of PP5-1F-MNP for PFOS, PFOA, and PFUnDA is of great significance to PFCs in the enriched environment.

[0129] Adsorption isotherm experiment: 10 mL of the above three PFCs mixed standard solutions diluted with ultrapure water at different concentrations were added to 15 mg of PP5-1F-MNP adsorbent material (the preparation process refers to the above other PFCs mixed standard solutions), and the concentrations were: 100 ng / mL, 200 ng / mL, 500 ng / mL, 1 μg / mL, 2 μg / mL, 5 μg / mL, 10 μg / mL, 20 μg / mL, 50 μg / mL, 75 μg / mL, 100 μg / mL, 150 μg / mL, 200 μg / mL. The mixture was vortexed on a vortex mixer for 8 minutes, and the solution and the material were separated by an external magnet. 1 mL of the upper solution was taken out and centrifuged. 90 μL of the supernatant was taken and 10 μL of 500 ng / mL was added. 13 C-PFOA and 13 The C-PFOS internal standard mixture was vortex mixed to make it fully mixed, and then detected by mass spectrometry, and each variable was repeated three times.

[0130] The adsorption capacity of PFCs is calculated as follows:

[0131]

[0132] Among them, Q e (mg / g) is the equilibrium adsorption capacity; C0 (μg / mL) is the initial concentration of PFCs; C e (μg / mL) is the equilibrium concentration of PFCs (obtained by mass spectrometry after adsorption equilibrium); V (mL) is the volume of PFCs solution; W (mg) is the mass of PP5-1F-MNP.

[0133] The results are as follows Fig.16 As shown in the figure, with the gradual increase of the initial concentration of a series of standard solutions, the adsorption capacity of PP5-1F-MNP for PFOA, PFOS, and PFUnDA also showed a corresponding increasing trend, which indicates that the surface active sites of PP5-1F-MNP can still effectively interact with these difficult-to-degrade PFCs under high concentration conditions, thereby enriching and removing them from the solution.

[0134] In order to further reveal the adsorption mechanism of the PP5-1F-MNP adsorbent material for these three PFCs, the Langmuir and Freundlich adsorption isotherm models were used to fit and analyze the experimental data. The Langmuir adsorption isotherm equation assumes that the solid surface of the adsorbent is uniform, the adsorption capacity of all adsorption sites is the same, there is no interaction between the adsorbed molecules, and it belongs to a monolayer adsorption effect. Adsorption and desorption are two reversible processes that maintain a dynamic equilibrium. The Freundlich adsorption isotherm equation assumes that there is a phenomenon of non-uniform adsorption on the adsorbent surface, that is, the adsorption capacity of the surface adsorption sites is different. Multilayer adsorption means that the adsorbed molecules can continue to adsorb on the already adsorbed molecules.

[0135] Langmuir adsorption isotherm equation:

[0136]

[0137] Among them, Q e (mg / g) is the equilibrium adsorption capacity; C e (μg / mL) is the equilibrium concentration of PFCs; Q m (mg / g) is the maximum adsorption capacity of PFCs; K L is the Langmuir adsorption constant.

[0138] Freundlich adsorption isotherm equation:

[0139]

[0140] Among them, Q e (mg / g) is the equilibrium adsorption capacity; K F is the Freundlich adsorption constant; is the heterogeneity constant.

[0141] Table 3 Fitting results of Langmuir equation and Freundlich equation

[0142]

[0143] By comparing the fitting results of the Langmuir adsorption isotherm equation and the Freundlich adsorption isotherm equation in Table 3, it was found that the Langmuir model fitting correlation coefficients of PFOA, PFOS and PFUnDA were 0.9955, 0.9976 and 0.9769, respectively. The Freundlich model fitting correlation coefficients were 0.9416, 0.9450 and 0.8073, respectively. The Langmuir model showed higher accuracy in describing the adsorption behavior of PP5-1F-MNP on PFCs. The model shows that the adsorption process of PFCs on PP5-1F-MNP is mainly monolayer adsorption, which means that the adsorption sites on the adsorbent surface are evenly distributed, and each adsorption site can only adsorb one PFCs molecule to form a dense monomolecular adsorption layer. The maximum adsorption capacity can be calculated by the adsorption isotherm equation. The maximum adsorption capacities for perfluorooctanoic acid (PFOA), perfluorosulfonic acid (PFOS) and perfluoroundecanoic acid (PFUnDA) are 42.02, 62.11 and 64.94 mg / g, respectively.

[0144] 4. Methodological Validation

[0145] Preparation of mixed standard solutions of 8 PFCs: Take 50 μL of 1 mg / mL standard stock solutions of PFOA, PFOS, PFNA, PFDA, PFUnDA, PFDoDA, PFTrDA and PFTeDA, mix them, add 600 μL of acetonitrile to dilute them into 50 μg / mL mixed standard solutions, and then dilute the 50 μg / mL mixed standard solutions with acetonitrile to 0.1 ng / mL mixed standard solutions.

[0146] 1) System suitability

[0147] Take 90 μL of the evenly mixed 0.1 ng / mL mixed standard solution, add 10 μL of the 10 ng / mL internal standard mixed solution, mix evenly, take 70 μL into the injection bottle, and detect on the HPLC-MS / MS according to the chromatographic conditions in this example to obtain the chromatogram of the standard.

[0148] Fig.17 The chromatograms are of 8 PFCs standards and a mixed solution of two isotope internal standards. Under the optimized chromatographic conditions, the 8 PFCs can be eluted sequentially within 10 minutes and present sharp peaks without tailing, indicating that there is no interference from matrix effects during the analysis process, and a strong response signal is obtained, proving the high efficiency and good separation performance of the method.

[0149] Take 90 μL of the above 0.1 ng / mL mixed standard solution, add 10 μL of 10 ng / mL internal standard mixed solution, mix well and take 70 μL into the injection bottle, and obtain a full scan mass spectrum by Q3 full scan detection on a high performance liquid chromatography-mass spectrometer according to the mass spectrometry conditions in this embodiment.

[0150] Fig.18 This is a full scan of 8 PFCs and two isotope internal standards in negative ion mode. Since the functional groups of PFCs are carboxyl or sulfonic acid groups, PFCs are more likely to be deprotonated to form [MH]- molecular ion peaks. The [MH]- ions of the 8 compounds can be seen in the figure.

[0151] 2) Linearity, limit of quantification, limit of detection

[0152] The performance of the PP5-1F-MNP MSPE-HPLC-MS / MS analysis method was comprehensively evaluated under optimized magnetic solid phase extraction conditions. The linear range, intra-day and inter-day precision, and correlation coefficient (R 2 ), limit of detection (LOD, S / N ≥ 3) and limit of quantification (LOQ, S / N ≥ 10) to comprehensively evaluate the accuracy, reliability and sensitivity of the method. The specific operation process is as follows:

[0153] Accurately measure 8 kinds of PFCs standard mixed solutions, dilute with HPLC grade acetonitrile to a series of standard solutions with concentrations of 0.01ng / mL, 0.02ng / mL, 0.05ng / mL, 0.1ng / mL, 0.2ng / mL, 0.5ng / mL, 1ng / mL, 2ng / mL, 5ng / mL, 10ng / mL, 20ng / mL, 50ng / mL, and 100ng / mL, centrifuge for 3 minutes, take 90μL of supernatant and add 10μL of internal standard mixed solution with a concentration of 10ng / mL, vortex mix, centrifuge for 3 minutes, and take 70μL of the solution after centrifugation to the injection bottle. In addition, use HPLC grade acetonitrile to prepare two blank variables, a single blank sample (acetonitrile with internal standard mixed solution) and a double blank sample (no analyte or internal standard, pure acetonitrile). HPLC-MS / MS direct injection, injection volume 5μL, each variable is measured three times in parallel.

[0154] The concentration of each compound in the series of mixed standard solutions (ng / mL) was used as the horizontal axis (X), and the ratio of the peak area of ​​each compound to the corresponding internal standard peak area was used as the vertical axis (Y) for weighted linear regression. The signal-to-noise ratio S / N ≥ 3 was defined as the detection limit (LOD), and S / N ≥ 10 was defined as the quantification limit (LOQ). The RSD was calculated using the peak area ratios measured three times. The results are shown in Table 4. Within the linear range, there was a significant linear correlation between the peak area ratios of the eight long-chain PFCs and their concentrations, and the correlation coefficient R2 The range of LOD was 1.0-2.8 ng / L, the range of LOQ was 2.0-10.0 ng / L, and the range of RSD was 1.7-6.3%. The experimental results showed that this method not only had high sensitivity, but also had good linearity.

[0155] Table 4

[0156]

[0157] Example 3: Detection of PFCs in actual water samples

[0158] This experiment collected natural water bodies from Nanhu Lake, Tangxun Lake, and Donghu Lake in Wuhan City, Hubei Province, as well as rainwater in Wuhan City as actual environmental samples for research. The collected water samples were stored in containers washed with deionized water to ensure the purity of the samples. The collected water samples were then filtered through a 0.22μm filter membrane to remove suspended particles and other impurities. Water samples that were not used immediately were placed in a refrigerator at 4°C and stored in the dark to prevent possible contamination or deterioration.

[0159] PP5-1F-MNP was used as a magnetic solid phase extraction adsorbent to enrich PFCs in actual samples. First, 15 mg of PP5-1F-MNP material was accurately weighed, and 10 mL of water sample was added to it. The material was vortexed on a vortex mixer for 5 minutes to allow the material to fully contact with the environmental water sample. Then, the material was separated from the solution under the action of a magnet, and 5 mL of pure water was added to wash away the residual and unadsorbed PFCs on the surface of the material. Then, 7 mL of chromatographic grade acetonitrile was added and vortexed for 8 minutes to desorb the PFCs adsorbed on the material. Under the action of an external magnet, 4 mL of the supernatant was taken for nitrogen blowing, and finally, it was re-dissolved with 200 μL of acetonitrile solution, and 90 μL of the re-dissolved solution was taken. 10 μL of 10 ng / mL was added to it. 13 C-PFOA and 13 The internal standard mixture of C-PFOS was vortexed and then detected according to the chromatography and mass spectrometry conditions in Example 2, and each variable was measured three times in parallel.

[0160] The experiment showed that no PFCs were detected in actual environmental water samples, which was consistent with the detection results of traditional biomass fluorinated material-assisted liquid chromatography-tandem mass spectrometry and covalent organic framework material-assisted liquid chromatography-tandem mass spectrometry.

[0161] The accuracy test was conducted using the water sample from Lake Thomson. The specific steps are as follows:

[0162] First, dilute the 1 mg / L mixed standard solution (directly use the solution under the accuracy test item in Example 2) with the above-mentioned treated Thompson Lake water sample to prepare three different concentration levels of test solutions: low (20 ng / L), medium (200 ng / L) and high (2000 ng / L). Take 10 mL of the test solution and add it to 15 mg of the PP5-1F-MNP material obtained in Example 1. Vortex on a vortex mixer for 5 minutes to allow the material to fully contact with the environmental water sample, and then separate the material from the solution under the action of a magnet, and add 5 mL of pure water to wash away the residual and unabsorbed PFCs on the surface of the material. Then add 7 mL of chromatographic grade acetonitrile and vortex for 8 minutes to desorb the PFCs adsorbed on the material. Take 4 mL of the supernatant under the action of an external magnet and blow it to dryness with nitrogen, and then re-dissolve it with 200 μL of acetonitrile. Take 90 μL of the re-dissolved solution and add 10 μL of 10 ng / mL 13 C-PFOA and 13 The internal standard mixed solution of C-PFOS was vortex mixed and then detected according to the chromatography and mass spectrometry conditions in Example 2. Each concentration was measured three times in parallel. The detection results are shown in Table 5, where the RSD was calculated from the peak area ratio of the three measurements.

[0163] After spiking, the average recoveries of low, medium and high concentrations ranged from 84.8% to 104.7%, and the RSD ranged from 0.61% to 13.1%. The established PP5-1F-MNP MSPE-HPLC-MS / MS method based on PP5-1F-MNP as a highly efficient adsorbent material showed good precision and stability. Therefore, it was shown that PP5-1F-MNP material has the potential to be used in the enrichment and analysis of PFCs in actual environmental water samples.

[0164] Table 5

[0165]

Claims

1. A magnetic cation column [5] aromatic polymer material PP5-1F-MNP, wherein the PP5-1F-MNP has Fe3O4 nanoparticles as the core, and the cation column [5] aromatic polymer PP5-1F is coated on the outside of the Fe3O4 nanoparticles. The structural formula of the PP5-1F is as follows:

2. A method for preparing the magnetic cation column [5] aromatic polymer material PP5-1F-MNP as described in claim 1, firstly, the bromine functional group column [5] aromatic hydrocarbon and 3-fluoropyridine undergo electrophilic substitution reaction to generate the cation column [5] aromatic hydrocarbon PP5-1F, then PP5-1F is reacted with FeCl3·6H2O in a high pressure reactor by a one-pot solvothermal method to construct the magnetic cation column [5] aromatic polymer material PP5-1F-MNP.

3. The preparation method according to claim 2, characterized in that: The preparation method comprises the following steps: (1) Preparation of 1,4-bis(2-bromoethoxy)benzene Under the condition of an ice water bath at 0°C, hydroquinone dihydroxyethyl ether and triphenylphosphine are added to anhydrous acetonitrile, and then carbon tetrabromide is slowly added under the protection of an inert gas, and then the reaction system is restored to room temperature, stirred at room temperature until the solution is clear and transparent, and then cold water is added to quench the reaction, and the product is purified and dried to obtain 1,4-bis(2-bromoethoxy)benzene; (2) Preparation of brominated functional group column [5] aromatic hydrocarbons Add paraformaldehyde to a solution of 1,4-bis(2-bromoethoxy)benzene, then add boron trifluoride etherate, stir at room temperature for 4-8 hours, after the reaction is completed, quench the reaction with cold water, purify and dry the product to obtain brominated functional group column [5] aromatic hydrocarbons; (3)PP5-1F Add the brominated functional group column [5] aromatic hydrocarbon to 3-fluoropyridine, heat the reaction mixture under reflux and stir for 8-12 hours, and after the reaction is completed, a yellow solid is obtained, which is purified and dried to obtain PP5-1F; (4)PP5-1F-MNP PP5-1F was added to ethylene glycol and dissolved by ultrasonic. Then FeCl3·6H2O and sodium acetate were added. After ultrasonic dispersion, the mixture was stirred evenly at room temperature. Then the mixture was transferred to a reactor and reacted at 100-250°C for 8-12h. The mixture was washed and dried to obtain a black magnetic column [5] aromatic polymer PP5-1F-MNP.

4. The preparation method according to claim 3, characterized in that: In the step (4), anhydrous ethanol and deionized water are used for alternate washing, and the drying step is: vacuum drying at 40° C. for 24 hours.

5. The preparation method according to claim 3, characterized in that: In step (1), the molar ratio of hydroquinone dihydroxyethyl ether to triphenylphosphine is 1:(2-3), and the molar ratio of triphenylphosphine to carbon tetrabromide is 1:1; and / or In step (2), the molar ratio of 1,4-bis(2-bromoethoxy)benzene, paraformaldehyde and boron trifluoride etherate is 1:(0.5-3):(0.5-1.5); and / or In step (3), the ratio of column [5] aromatic hydrocarbon to 3-fluoropyridine is 0.3-1.2 mmol: 5-10 mL; and / or In step (4), the ratio of PP5-1F to ethylene glycol is 0.5-2 g: 10-30 mL; and / or In step (4), the molar ratio of PP5-1F to FeCl3·6H2O and sodium acetate is (0.05-0.5):1:(2-8).

6. Use of the PP5-1F-MNP according to claim 1 or the PP5-1F-MNP prepared by any one of the preparation methods according to claims 2 to 5 in pollutant adsorption.

7. Use of the PP5-1F-MNP according to claim 1 or the PP5-1F-MNP prepared by any one of the preparation methods according to claims 2 to 5 in the adsorption of perfluorinated compounds.

8. A method for detecting the content of PFCs based on magnetic solid phase extraction-high performance liquid chromatography tandem mass spectrometry of the PP5-1F-MNP: (1) Chromatographic conditions Chromatographic column: C18 column; Mobile phase A: 5mmol / L ammonium acetate aqueous solution, mobile phase B: acetonitrile; Flow rate: 0.4 mL / min; Column temperature: 40°C; Gradient elution conditions: (2) Mass spectrometry conditions An electrospray ionization source was used to ionize in negative ion mode, and multiple reaction monitoring mode MRM was established to analyze each PFCs; nebulizer gas flow rate: 3 L / min, heating gas flow rate: 10 L / min, drying gas flow rate: 10 L / min, interface temperature: 300 °C, DL temperature: 250 °C, heating block temperature: 400 °C, and each MRM dwell time was 12 ms; (3) Magnetic solid phase extraction step After mixing PP5-1F-MNP with the PFCs sample solution to be tested, vortex operation is performed on a vortex mixer for 2-15 minutes to ensure that the PP5-1F-MNP adsorbent fully and selectively adsorbs PFCs. The external magnet quickly separates the PP5-1F-MNP adsorbent from the solution. The PP5-1F-MNP is washed with pure water to remove the PFCs not adsorbed on the surface. Desorption liquid is added and vortexed for 3-15 minutes to desorb the PFCs adsorbed by the PP5-1F-MNP. After separating the PP5-1F-MNP from the solution, a certain amount of solution is taken, concentrated to dryness, and then the desorption liquid is added to redissolve the PFCs. The re-dissolved solution is taken for HPLC-MS / MS detection.

9. The method according to claim 8, characterized in that The desorption liquid is dichloromethane, ethyl acetate, acetone, methanol or acetonitrile; and / or The ratio of the PP5-1F-MNP adsorbent to the desorption liquid is (5-20) mg: (3-13) mL; and / or When the reconstituted solution is subjected to HPLC-MS / MS detection, the internal standard method is used to detect the content of PFCs. 13 C8-PFOA and 13 C8-PFOS was used as an internal standard.

10. The method according to claim 8, characterized in that The PFCs are long-chain PFCs with a carbon chain of not less than 8.

Citation Information

Patent Citations

  • Cationic water-soluble column [5] aromatic hydrocarbon and preparation thereof and application of cationic water-soluble column [5] aromatic hydrocarbon in silver ion detection serving as acceptor

    CN104447363A

  • Analysis and detection method of perfluorinated compound

    CN112229935A

  • Method for detecting perfluoroalkanoic acid compound in aquatic product by enrichment purification-liquid chromatography tandem mass spectrometry and application

    CN112684030A

  • MACROCYCLIC AND CAGE-LIKE MOLECULE BASED ON BIPHEN[n]ARENE AND DERIVATIVE, SYNTHESIS METHOD AND USE THEREOF

    US20230192692A1

  • Hydrophilic magnetic resin with high specific area, preparation method therefor and application method thereof for rapidly extracting phthalates in water body

    WO2015024520A1

Cited By

  • Magnetic nanoparticle / pillararene covalent organic framework core-shell material and application thereof

    CN118142496A

  • Magnetic nanoparticles / pillar aromatic covalent organic framework core-shell materials and their applications

    CN118142496B